THE IMPACTS OF CULTURE IN ENGLISH LANGUAGE TEACHING FOR VIETNAMESE STUDENTS AS SEEN FROM THE PERSPECTIVES OF AMERICAN TEACHERS AND VIETNAMESE STUDENTS = Tác động của văn hóa khi giảng dạy tiếng Anh cho học sinh Việt Nam dưới góc nhìn của giáo viên người Mỹ và học sinh Việt Nam - Nguyễn, Thu Phương (2020)
The research was conducted to present cultural impacts from the viewpoints of both native teachers and learners from Vietnam. Semi-structured interview was employed as the main method to collect data, and content analysis was applied for data analysis. Three teachers coming from America and four students from University of Languages and International Studies (ULIS) and Hanoi University of Science (HUS) were chosen to be the participants. The findings indicated that Vietnamese students have passive learning attitude, which is shown in the way they are reluctant to raise their own opinions and only learn what they are taught at schools. Moreover, differences in Asian and western teaching methods also caused difficulties for lesson efficiency. To address the problems, American teachers made efforts to enrich Vietnamese culture and modify teaching methods and techniques which are appropriate to students‟ learning styles. The research suggests that American or native teachers should be aware of Vietnamese cultural values as well as language before coming to Vietnam. Maintaining contacts with students and learning from local people are some effective ways to bridge the gap between Vietnamese and American cultures.